2021
DOI: 10.30798/makuiibf.910364
|View full text |Cite
|
Sign up to set email alerts
|

Kirilgan Seki̇zli̇'de Gida Fi̇yat Balonlarinin Saptanmasi: Küresel Kri̇z-Covi̇d 19 Pandemi̇ Dönemleri̇ İçi̇n Karşilaştirma

Abstract: Pandemi Dönemleri İçin Bir Karşılaştırma" başlıklı bildirinin gözden geçirilmiş ve genişletilmiş halidir. Öz Çalışmanın amacı, 2008 Küresel Kriz ve Covid 19 pandemi dönemlerinde Kırılgan Sekizli ülkelerinde gıda fiyat balonlarının tarihlerini saptamaktır. Bu amaçla yinelemeli sağ kuyruklu birim kök testleri (Sup-Augmented Dickey-Fuller; SADF ve Generalized Sup-Augmented Dickey-Fuller; GSADF) yoluyla 2007:01-2020:09 dönemi için FAO gıda fiyat endeksi kullanılarak gıda fiyat balonlarının tarihleri tahmin edilmek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Four distinct bubble formations may be seen when the bubble formation times for the IMF variable are examined. Similar to [1,3,59,[61][62][63][64]66,68,[88][89][90][91] the results of the study suggest that there were many food price bubbles in the period under consideration. A small number of studies [16,18,60] in the literature failed to reach the bubble formations or concluded that very few bubbles formed.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Four distinct bubble formations may be seen when the bubble formation times for the IMF variable are examined. Similar to [1,3,59,[61][62][63][64]66,68,[88][89][90][91] the results of the study suggest that there were many food price bubbles in the period under consideration. A small number of studies [16,18,60] in the literature failed to reach the bubble formations or concluded that very few bubbles formed.…”
Section: Discussionsupporting
confidence: 58%
“…In her study, Varlık [66] examined the existence of food price bubbles between January 2007and September 2020 with the help of SADF and GSADF tests. In the study, food price bubbles in eight fragile countries were analyzed using FAO food price index data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Varlık (2021) examined the food price bubbles that occurred during the 2008 global crisis and the Covid-19 period in countries defined as the Fragile Eight. According to the empirical results of the study, price bubbles occurred in the Fragile Eight countries during both the 2008 global crisis and the Covid-19 pandemic.…”
Section: Literaturementioning
confidence: 99%
“…This is because developing measures to combat inflation and prevent food prices from rising is of great importance in ensuring longterm and sustainable price stability (Eştürk and Albayrak, 2018). Considering the fact that most of the increase in inflation is due to the increase in food prices, central banks should prioritize the necessary measures to prevent the growth of food price bubbles in the current period (Varlık, 2021). These increases in the prices of foods that are vital to consumers cause consumers to become victims and their quality of life to decrease (Cavlak and Selvi, 2022).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%